2001
DOI: 10.1002/1097-0142(20010901)92:5<1101::aid-cncr1426>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with cisplatin and etoposide in patients with neuroendocrine tumors

Abstract: BACKGROUND Patients with malignant endocrine pancreatic tumors (EPTs) are responsive to combinations of chemotherapy with streptozotocin and 5‐fluorouracil/doxorubicin, whereas patients with malignant carcinoids are not. For both categories of patients, α‐interferon and/or somatostatin analogs can produce long‐lasting responses. Cisplatin in combination with etoposide has been suggested to be effective in patients with malignant neuroendocrine carcinomas. The authors used this therapy as second‐line or third‐l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
101
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(106 citation statements)
references
References 10 publications
2
101
0
3
Order By: Relevance
“…Indeed, in undifferentiated NETs, the chemosensitivity is similar to that of small cell carcinoma of the lung. Various combinations of chemotherapy have been used, including streptozotocin and adriamycin in well-differentiated pancreatic NETs (Moertel et al 1992), lomustine (CCNU) and 5-fluorouracil (5FU) in advanced NETs (Kaltsas et al 2002), etoposide (VP16) and cisplatin (CDDP) (Moertel et al 1991, Fjallskog et al 2001 in poorly-differentiated, aggressive NETs giving response rates of 50 to 56% and benefitting pancreatic NETs and foregut carcinoids most. However, toxicity rates were high.…”
Section: Interferon-alpha and Chemotherapy For Gut Neuroendocrine Tummentioning
confidence: 99%
“…Indeed, in undifferentiated NETs, the chemosensitivity is similar to that of small cell carcinoma of the lung. Various combinations of chemotherapy have been used, including streptozotocin and adriamycin in well-differentiated pancreatic NETs (Moertel et al 1992), lomustine (CCNU) and 5-fluorouracil (5FU) in advanced NETs (Kaltsas et al 2002), etoposide (VP16) and cisplatin (CDDP) (Moertel et al 1991, Fjallskog et al 2001 in poorly-differentiated, aggressive NETs giving response rates of 50 to 56% and benefitting pancreatic NETs and foregut carcinoids most. However, toxicity rates were high.…”
Section: Interferon-alpha and Chemotherapy For Gut Neuroendocrine Tummentioning
confidence: 99%
“…The genetic, pathological and clinical features of PDNECs overlap with those of small cell lung cancer, thereby combined chemotherapy with cisplatin and etoposide has been widely used for extrapulmonary PD-NECs (18,19). In addition, several clinical studies reported that this combination was effective for improving survival time of patients with metastatic NECs of the GI tract (18,20). However, to the best of our knowledge, only one study examined the efficacy of this treatment as first line chemotherapy for unresectable PD-NECs of the pancreas and hepatobiliary tract (22), but this combination therapy exerts only marginal antitumor activity and severe toxicity, and resulted in median progression-free survival and overall survival of 1.8 and 5.8 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Two trials of cisplatin and etoposide in 45 and 32 evaluable patients produced response rates of 67% and 53%, respectively. 85,86 Whether there is a distinct clinical phenotype of a more NE-differentiated cancer remains unknown. Patients with poorly differentiated prostate cancers who are diagnosed later with unusual visceral metastases, such as hepatic or brain, are often assumed to have some component of NE differentiation but rarely undergo biopsy.…”
Section: Ne Differentiation In Hrpcmentioning
confidence: 99%